Pengaruh Kualitas Kredit, Biaya Operasional Pendapatan Operasional dan Profitabilitas terhadap Permodalan Bank Perekonomian Rakyat di Indonesia per Triwulan Tahun 2021 – 2022 - Mangasa Tua, Rudy Bodewyn; Arini, Dewi Ulfah (Jurnal Disrupsi Bisnis, 2024)
The purpose of this study is to find out the effects of Non Performing Loan (NPL), Operational costs versus operational income (BOPO) and Profitability ( ROA) against Capital (CAR) People Economy Bank either partially or simultaneously.Research methods using descriptive qualitative, the object of research is a nationally conventional bpr.First quarter of 2021 to fourth quarter of 2022 data obtained from the financial services authority statistics report.The conclusions drawn from this study are npl, bopo and roa both partially and simultaneously have no influence on roa on bpr in indonesia period of 2021-2022.